2008
DOI: 10.1111/j.1365-4632.2008.03549.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow in necrobiosis lipoidica diabeticorum*

Abstract: Our findings refute the hypothesis that NLD is a manifestation of microvascular ischemic disease of the skin. The increased blood flow seen in NLD lesions suggests an ongoing inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
1
26
0
6
Order By: Relevance
“…Without dispute there is a strong correlation for necrobiosis lipoidica particularly with diabetes mellitus. A study using Doppler flowmetry showed that necrobiosis lipoidica is improbable to be due to microvascular ischaemia, but rather can be caused by inflammation (42). This suggests that ulcerating necrobiosis lipoidica can be seen as part of a generalised inflammatory reaction due to a systemic metabolic syndrome.…”
Section: Necrobiosis Lipoidica -A Systemic Inflammatory Disease?mentioning
confidence: 97%
“…Without dispute there is a strong correlation for necrobiosis lipoidica particularly with diabetes mellitus. A study using Doppler flowmetry showed that necrobiosis lipoidica is improbable to be due to microvascular ischaemia, but rather can be caused by inflammation (42). This suggests that ulcerating necrobiosis lipoidica can be seen as part of a generalised inflammatory reaction due to a systemic metabolic syndrome.…”
Section: Necrobiosis Lipoidica -A Systemic Inflammatory Disease?mentioning
confidence: 97%
“…Duration of the heating to obtain maximum vasodilation: in five studies the skin was heated for less than 20 min [42, 4447], while in eight studies heating was applied for 20 min or more [43, 4854]. There were three locations of measurements: eight studies measured on the forearm [42, 43, 4648, 5254], three on the pretibial surface of the leg [4951], and two on the quadriceps muscle [44, 45]. …”
Section: Resultsmentioning
confidence: 99%
“…Investigators think an inflammatory process is more influential in the pathogenesis than small vessel occlusions. 12 Collagen Collagen abnormalities are seen at the level of the collagen fibrils. Absent cross striations are the most prominent finding, with some cases even showing a complete loss of collagen and elastin.…”
Section: Blood Vesselsmentioning
confidence: 98%